Autograft vs Allograft With Bone Marrow Aspirate Concentrate as an Osteotomy Gap Filler in Lateral Column Lengthening for Progressive Collapsing Flatfoot Deformity - Ramesh Radhakrishnan MBBS, MRCS(Eng); Don Thong Siang Koh MBBS, BSc(Hon), MRCS, MMED(Ortho); Eric Wei Liang Cher MD, MRCS, MMed(Ortho), FRCSEd(Ortho); Wenxian Png MBBS, MMed(Ortho), MRCSEd, FRCSEd(Ortho); Inderjeet Rikhraj Singh MBBS, FRCS, FAMS, MHPE (Maastricht) (Foot & Ankle Orthopaedics)
Background: Progressive collapsing flatfoot deformity (PCFD) is a complex condition characterized by hindfoot valgus, midfoot varus, and forefoot abduction, leading to functional impairment and pain. Surgical correction often includes lateral column lengthening (LCL), which addresses structural deformity and restores alignment. Autografts remain the gold standard as an osteotomy gap filler for LCL despite donor site morbidity. Allografts augmented with patient’s own bone marrow aspirate concentrate (BMAC) offer a potential alternative because of their osteogenic properties. This study compares the clinical and radiologic outcomes of autografts vs allografts with BMAC in LCL for PCFD. Methods: This retrospective study reviewed 38 patients who underwent LCL for PCFD at a tertiary institution from 2012 to 2022. Patients were divided into 2 groups: the 25 who received autografts (group A), and the 13 who received allografts (group B) mixed with BMAC. Clinical outcomes were assessed using visual analog scale (VAS), American Orthopaedic Foot & Ankle Society (AOFAS) ankle-hindfoot scores, and 36-Item Short Form Health Survey (SF-36) scores at 6 and 24 months postoperatively. Radiologic union was evaluated through serial weightbearing radiographs at regular interval post-surgery. Results: Both groups A and B achieved radiologic union at an average of 5.64 ± 1.80 and 5.15 ± 2.58 months, respectively. There were no cases of delayed union or nonunion. Both groups demonstrated significant improvements in VAS, AOFAS, and SF-36 scores at 6 and 24 months, with no statistically significant differences in outcomes. Group A had 2 cases of peroneal tendinopathy, 1 case of peroneal tendon adhesion to the plate, 1 case of screw prominence, and 1 case of chronic pain attributed to plantar nerve irritation. Group B had no reported complications. Conclusion: This study suggests that allografts augmented with BMAC may be a viable alternative to autografts for LCL in PCFD, offering comparable union rates and functional outcomes. However, as a retrospective cohort study with a small sample size, further prospective research is needed to confirm these findings. Level of Evidence: Level III, retrospective cohort studies.